P-16 UNLOCKING S-PINDOLOL'S POTENTIAL FOR MASLD: BENEFICIAL EFFECTS ON MUSCLE MASS AND FUNCTION AND LIVER HISTOLOGY IN WESTERN- DIET FED MICE - Daniel Cabrera; Loreto Aguilar; Faride Saud; Lisbell Estrada; Marcelo Andia; Marco Arrese; Juan Pablo Arab; Luis Antonio Diaz; Francisco Barrera; Rene Baudrand; Claudio Cabello-Verrugio (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) is linked to sarcopenia, which worsens disease's prognosis. The complex liver-muscle crosstalk opens the possibility that improvements in muscle quantity and quality may be directly beneficial for MASLD. This study investigates the effects of s-pindolol, a beta-blocker known for its anabolic properties, on both muscle mass and function as well as on MASLD progression in mice. Patients / Materials and Methods: Male C57BL6 mice were subjected to a western diet (WD) for 20 weeks to induce MASLD and then mice were randomly grouped and treated with 3 mg/kg s-pindolol twice a week or left untreated. Assessments included grip and isolated muscle strength, body composition via bioimpedance spectroscopy, Abdominal MRI, liver histology, serum analyses and gene expression profiling. Results and Discussion: S-pindolol reduced liver steatosis and inflammation and was associated with lower levels of MCP-1, IL-10, TGF-β, and ACACA (Acetyl-CoA Carboxylase Alpha). S-pindolol also counteracted IGF-1 serum levels reduction seen in WD-fed mice. In addition, S-pindolol treatment led to an increase in muscle mass as confirmed by bioimpedance spectroscopy and MRI techniques. While exercise performance remained unchanged, grip strength improved together with a reduction in myosteatosis suggesting enhanced muscle quality. This was supported by an increase in muscle fiber diameter, indicating muscular hypertrophy independent of exercise. Conclusions: S-pindolol treatment ameliorates MASLD and enhances muscle quality in WD-fed mice. It may be hypothesized that s-pindolol's positive effects on muscle mass and function could play a role in its beneficial effects on MASLD through improvement of secretion of various salutary myokines. The present data underscore S-pindolol's therapeutic potential in MASLD.